A case study on the transformation of Chinese opera radio under the ecological environment of media integration - Bao, Fengbo; Razi, Siti Aishah Binti Hj Mohammad; Yasin, Megat Al Imran Bin (Redfame Publishing Inc., 2024)
Chinese opera is one of the important art forms in Chinese traditional culture that has a long history and rich forms of expression. Media integration in Chinese opera broadcasting refers to the combination of traditional opera art forms with modern broadcasting technologies to meet the communication needs and technological development trends of contemporary society. This study investigated the state of media development based on the media ecology theory. This study explored media integration in Chinese opera broadcasting using case study methodology to describe multimedia communication methods adopted by the broadcasting stations to increase the listening rate. Study subjects were three Chinese opera radio programs. The research results show that Chinese Opera broadcasting has begun to use various media technologies to carry out media integration development, inject new vitality into traditional art forms, and increase the appeal to contemporary audiences. The research also found that with the continuous progress of technology, Chinese Opera broadcasting will have greater space for development in the future and bring better listening experience to the audience.